Answer:
3x + 6
Step-by-step explanation:
3(x + 2)
= 3(x) + 3(2)
= 3x + 6
Answer:
p = -5
every element in the sequence is created by subtracting 3 from the pervious element.
Step-by-step explanation:
I am not sure you put every necessary information here.
but I'd the visible information is truly everything, then it's is trivial.
the difference between 4 and 1 is ... well, -3. meaning we subtract 3 from 4 to get 1.
we suspect this is the rule and keep trying.
1 -3 = -2
hey it works.
and -8 -3 = -11
hey, also correct.
and the difference between -2 and -8 is -6, and when we place another item in between (p), we cut that in half again to -3. so, it is all consistent.
therefore,
p = -2 -3 = -5
the rule is
an = an-1 - 3
Answer:
Step-by-step explanation:
-32/15/-4/5
-32/15*5/-4
-32*5/15*-4
-160/-60
8/3
Answer:
no
Step-by-step explanation:
4x -3 = 16
x=19/4
4(x-3) = 16: Distribute the number in the parenthesis with 4 and you get:
4x-12=16
x=7
4x-12=16 is not the same as 4x-3=16
Therefore they do not have the same solution.